Does Physical Proximity Influence Knowledge about the Structure and Formation of Volcanoes? An Empirical Case Study at Two German Schools in Ecuador - Otto, Karl-Heinz; Toulkeridis, Theofilos; Edler, Dennis (Journal of Geography Education, 2020)
Ecuador is characterized by the highest density of high-risk volcanoes worldwide. Does this affect students' knowledge of volcanism? This paper provides partial results of a comprehensive overall study of the knowledge of students from Ecuador about the structure and development of volcanoes/volcanism. The study used a questionnaire administered to sixth-grade students without prior formal training on volcanoes and volcanism. Twelfth-grade students also This questionnaire was also answered by high school students. In addition, the questionnaire was also presented to twelfth-graders. The results of this sub-study indicate an influence of the proximity to high-risk volcanoes on the knowledge about the formation and structure of volcanoes/volcanism.
Keywords: students’ concepts, process-related knowledge, volcanoes/volcanism, Ecuador, education for sustainable development